1989
DOI: 10.1111/j.1440-1827.1989.tb01488.x
|View full text |Cite
|
Sign up to set email alerts
|

Endocardium of the Left Ventricle in Volume‐loaded Canine Heart

Abstract: To investigate the effects of volume loading of the heart, the endocardium was studied histologically and ultrastructurally. Thirteen adult female beagle dogs were used. An arterio-venous shunt was constructed between the right common carotid artery and the right external jugular vein in nine animals to induce a volume load. Four animals were used as controls. All were kept for 6-12 months. Heart weight, relative heart weight (heart weight/body weight), cardiac output index, stroke volume index and volumes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The role of the EE in these diseases has only recently been addressed. Typical morphological EE cellular lesions have now been described in conditions of ventricular volume (361) or pressure (81, 541) overloading, in experimental diabetes FIG. 11. Role of endothelial dysfunction in the progression of chronic cardiac failure.…”
Section: Cardiac Endothelial Dysfunction In Cardiac Failurementioning
confidence: 94%
“…The role of the EE in these diseases has only recently been addressed. Typical morphological EE cellular lesions have now been described in conditions of ventricular volume (361) or pressure (81, 541) overloading, in experimental diabetes FIG. 11. Role of endothelial dysfunction in the progression of chronic cardiac failure.…”
Section: Cardiac Endothelial Dysfunction In Cardiac Failurementioning
confidence: 94%
“…Since bFGF has been shown to play a role in autocrine growth regulation (44) and migration (29) of the endothelial cell, this high shear-induced increase may be relevant to the observed long-term increase in endothelial density that is oh served following surgically induced increases in blood flow in the canine carotid artery arteriovenous shunt model (4 4 h. In contrast our study showed that both physiological moderate ( 15 dyn/cm2) and elevated ( 36 dyn/cm2) shear stress induced a marked four-to fivefold decrease in PDGF B chain mRNA by 6-9 h. The BAE cells, unlike HUVE cells, express the B but not the A chain ofPDGF (39); the difference in the results may be due to the difference in cell origin. Furthermore, changes in mRNA levels were not reported for durations of shear > 4 h, the time after which the downregulation reported in the present work is most significant.…”
Section: =2060mentioning
confidence: 99%
“…We also hypothesized that shear stress may affect the expression of bFGF in light of the findings ofincreased endothelial density in response to step increases to high flow and resulting high shear stress (4). We have evaluated the in vitro effect of fluid shear stress of physiological moderate (15 dyn/cm2) and elevated (36 dyn/cm2) magnitude on the morphological properties and extent of cell shape change in confluent BAE monolayers and on mRNA levels of PDGF-B and bFGF using a previously described cone-plate apparatus (20).…”
Section: Introductionmentioning
confidence: 99%